A Neanderthal from the Central Western Zagros, Iran. Structural reassessment of the Wezmeh 1 maxillary premolar. Issue 135 (October 2019) - Zanolli, Clément; Biglari, Fereidoun; Mashkour, Marjan; Abdi, Kamyar; Monchot, Hervé; Debue, Karyne; Mazurier, Arnaud; Bayle, Priscilla; Le Luyer, Mona; Rougier, Hélène; Trinkaus, Erik; Macchiarelli, Roberto
Abstract: Wezmeh Cave, in the Kermanshah region of Central Western Zagros, Iran, produced a Late Pleistocene faunal assemblage rich in carnivorans along with a human right maxillary premolar, Wezmeh 1, an unerupted tooth from an 8 ± 2 year-old individual. Uranium-series analyses of the fauna by alpha spectrometry provided age estimates between 70 and 11 ka. Crown dimensions place the tooth specimen at the upper limits of Late Pleistocene human ranges of variation. Wezmeh 1 metameric position (most likely a P 3 ) remains uncertain and only its surficial morphology has been described so far. Accordingly, we used microfocus X-ray tomography (12.5 μm isotropic voxel size) to reassess the metameric position and taxonomic attribution of this specimen. We investigated its endostructural features and quantified crown tissue proportions. Topographic maps of enamel thickness (ET) distribution were also generated, and semilandmark-based geometric morphometric analyses of the enamel-dentine junction (EDJ) were performed. We compared Wezmeh 1 with unworn/slightly-moderately worn P 3 and P 4 of European Neanderthals, Middle Paleolithic modern humans from Qafzeh, an Upper Paleolithic premolar, and Holocene humans. The results confirm that Wezmeh 1 represents a P 3 . Based on its internal conformation and especially EDJ shape, Wezmeh 1 aligns closely with Neanderthals and is distinct from the fossil and extant modern human pattern of our comparative samples. Wezmeh 1 is thus the first direct evidence of Neanderthal presence on the western margin of the Iranian Plateau.